MODIFICATIONS OF VOWELS IN CONNECTED SPEECH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article gives information about in connected speech vowels can change their quality under the influence of other sounds.